2016
DOI: 10.1093/nar/gkw552
|View full text |Cite
|
Sign up to set email alerts
|

eIF1A/eIF5B interaction network and its functions in translation initiation complex assembly and remodeling

Abstract: Eukaryotic translation initiation is a highly regulated process involving multiple steps, from 43S pre-initiation complex (PIC) assembly, to ribosomal subunit joining. Subunit joining is controlled by the G-protein eukaryotic translation initiation factor 5B (eIF5B). Another protein, eIF1A, is involved in virtually all steps, including subunit joining. The intrinsically disordered eIF1A C-terminal tail (eIF1A-CTT) binds to eIF5B Domain-4 (eIF5B-D4). The ribosomal complex undergoes conformational rearrangements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 49 publications
4
71
4
Order By: Relevance
“…In order to test whether eIF2α-NTD and -CTD interact with each other, we combined NMR chemical shift perturbation (CSP) assays ( 27 , 29 , 30 ) with deletion analysis, comparing peak movements between spectra of full length eIF2α and spectra of eIF2α-NTD and -CTD alone. This approach is effective for observing dynamic interactions ( 28 , 38 ). We collected transverse relaxation optimized spectroscopy heteronuclear single-quantum coherence (TROSY-HSQC) NMR spectra of 2 H/ 15 N-labeled full length eIF2α and its individual domains.…”
Section: Resultsmentioning
confidence: 99%
“…In order to test whether eIF2α-NTD and -CTD interact with each other, we combined NMR chemical shift perturbation (CSP) assays ( 27 , 29 , 30 ) with deletion analysis, comparing peak movements between spectra of full length eIF2α and spectra of eIF2α-NTD and -CTD alone. This approach is effective for observing dynamic interactions ( 28 , 38 ). We collected transverse relaxation optimized spectroscopy heteronuclear single-quantum coherence (TROSY-HSQC) NMR spectra of 2 H/ 15 N-labeled full length eIF2α and its individual domains.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed downregulation of DUSP10 was associated with HCC metastasis [ 38 ]. EIF5B , one of eukaryotic translation initiation factors, was demonstrated to be involved in cell-cycle arrest in case of up-regulation [ 39 , 40 ]. MNAT1 , a factor of the CDK-activating kinase (CAK) enzymatic complex, is vital to transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Cryo-EM reconstructions of termination- or recycling-related complexes revealed that the NBD-containing core of ABCE1, when bound to ATP, occupies the GTPase-binding center and its FeS cluster domain binds and stabilizes the release factor eRF1 25 or the archaeal mRNA surveillance factor aPelota, 14 respectively. Strikingly, compared with the Pyrococcus abyssi 23 crystal structure, the new tentative model of the m48S IC proposed here indicates that ABCE1 could adopt a novel conformation, unobserved previously, where the NDB binding domains are in a fully closed conformation and the FeS cluster domain is rotated by ∼180° to acquire a proper orientation for direct binding to the 40S h44 ( Fig.…”
Section: Introductionmentioning
confidence: 99%